THE INFLUENCE OF ADOBE FLASH-BASED LEARNING MEDIA ON INTEREST IN LEARNING MATHEMATICS - Deiby Neltje Fransiska Tiwow; Henny Nikolin Tambingon; Viktory Nicodemus Joufree Rotty; Edino Ayub Lomban; Navel Oktaviandy Mangelep (Journal of Education and Teaching Learning, 2022)
The study aimed to determine the effect of Adobe Flash-based learning media on interest in learning mathematics. The type of research is Quasi-Experimental Quantitative with the "One Groups Pretest-Posttest Design" model. The population and subject are Catholic Elementary School 03. ST Yohanes Mapanget Barat with 22 respondents. Collecting data through interviews, questionnaires, and observations using SPSS-assisted regression analysis techniques. The results of the study showed that the hypothesis test obtained a signed value of 0.000 <0.05 and the results of the t-test obtained a Tcount of 7.252 > Ttable of 1.721, both of which showed that MPBAF variable and the variable interest in learning had a significant effect. R2 calculation obtained a correlation value of 98.2% this value indicates that the influence between the two variables is very large. In conclusion, the variable MPBAF and the variable interest in learning have a significant effect on interest in learning mathematics.